Integrating Stakeholder Knowledge Through a Participatory Approach and Semi-Quantitative Analysis for Local Watershed Management - Jofri Issac; Robert Newell (Systems)
Watersheds are threatened by numerous issues, such as climate change, population growth, urban expansion, and industrial development. These issues are complex and interconnected, and effectively addressing them requires integrating the values, knowledge, and expertise of various governing bodies, local organizations, and community members, all of whom have their own viewpoints and priorities. The current study employs a participatory approach and systems lens to engage different stakeholders in the complexity of watershed issues and management approaches. Using participatory modeling and semi-quantitative scenario analysis techniques, the study identifies relationships among watershed values, challenges, and strategies as well as the dynamics of these relationships. A fuzzy cognitive map was developed, which consists of 53 nodes (i.e., 13 values, 12 challenges, and 28 strategies) and 113 connections. Biodiversity, mental health, and sense of place emerged as key values, as they exhibited high centrality values when analyzing the system, and challenges like invasive species and urban sprawl were found to exert considerable impacts on these values. Strategies such as establishing and expanding greenspace, community stewardship, and governance-based interventions were identified as critical for addressing watershed challenges and enhancing watershed values. The study identified a series of governance-based strategies that focus on resource allocation, participatory governance, and institutional collaboration to address watershed management challenges as well as a set of engagement-based strategies that focus on environmental communication and public awareness. The study demonstrates the potential that participatory modeling and semi-quantitative analysis techniques can have for integrating both tangible, measurable values and intangible, difficult-to-measure values into planning and policymaking. The research reinforces the idea that local governments play a critical role in fostering inclusive and collaborative watershed management strategies.